Technical involvements and pressure applied influence movement demands in elite Australian Football Match-play - Vella, A.; Clarke, A. C.; Kempton, T.; Ryan, S.; Holden, J.; Coutts, A. J. (Science and Medicine in Football, 2022)
Match activity analyses in Australian Football (AF) have provided information on the loads of match-play and identified contextual factors influencing physical activity. Match physical activity has been shown to be influenced by technical and tactical factors. This study examined the association of in-game contextual factors and technical involvements on the activity demands of elite AF players. Global positioning system data were recorded from 35 players in 13 matches throughout the 2019 Australian Football League (AFL) season. Technical involvements - player possession, and defensive pressure applied - were attained from Champion Data (AFL statistics provider), while possession phases and the commencing possession chain event were manually coded. Mixed models examined the influence possession chain contextual factors had on the total distance (TD) and high-speed running (HSR). During attacking phases, physical activity increased when a player had a possession, when a greater number of opposition players applied pressure, and when play was initiated from a turnover (p = 0.001). During defensive phases, physical activity was greatest when an individual player applied pressure, however, also increased when the total number of players applying pressure increased and when play was initiated from a turnover or kick-in (p = 0.001). Overall, this study combines the three constructs of AF performance (physical, technical and tactical) and demonstrates that TD and HSR demands are greatest in a chain when a player was directly involved in the play or applying pressure on the opposition.